Crisis, Stimulus Package and Migration in China - Mária Csanádi; Nie Zihan; Li Shi (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
Authors of this paper trace the influence of the 2008 global crisis and the impact of the subsequently implemented stimulus package on the characteristics of migrant flow in China until 2012. They analyze the consequences of the temporary but dramatic economic set-back on migrant employment and that of the booming investments incited by the stimulus package. The paper reveals that the set-back caused dramatic temporary rise of migrant unemployment; it also had regional character due to the coastal concentration of exports hit by the crisis, determining earlier the direction of migrant flow. Regional priorities of the stimulus package reinforced the redirection of migrants away from the coast towards central and western regions. Migration routes also shortened partly because migrants's destination shifted closer to their home-town region and also by increasingly finding workplace within their own province during the researched period. The stimulus package restructured migrant routes of the pre-crisis period not only according to its regional priorities, but also according to sectoral priorities from manufacturing towards the construction sector. The restructuring, combined with increased number of migrants, shows both temporary and steady features as migrants adapt to the dynamics of the impact of the stimulus package and to respective economic reactions.
Keywords: E24; R23; P23; F5; R2; J08; 330; migration; employment; stimulus package; crisis; spacial disparities; China